Anisotropic behaviours of droplets impacting on dielectrowetting substrates - Vo, Quoc (2021)
The spreading of a sessile droplet on a solid substrate is enhanced if a non-uniform electric field is applied at the contact-line region. This so-called dielectrowetting effect holds great potential in controlling the spreading of droplets by varying the strength of the electric field. In this paper, we experimentally and theoretically study the effect of the dielectrowetting on the dynamics of droplets impacting on a solid surface having electrodes to impose the non-uniform electric field to the liquid. We experimentally study the anisotropic behaviours in both the spreading and retracting stages: the droplets spread more but retract with significantly smaller rates in the direction parallel to the electrodes. We provide a theoretical explanation for the spreading enhancement caused by dielectrowetting by decoupling it from inertia-induced spreading. We also theoretically account for the reduction in retraction rate using force balance at the contact line. The theoretical analysis in both the spreading and retracting stages is verified experimentally.